Assessment of semi-permanent hair dyes in wash water from beauty salons by liquid chromatography-tandem mass spectrometry-selected reaction monitoring (LC-MS/MS-SRM) - Franco, Jefferson Honorio [UNESP]; Da Silva, Bianca F. [UNESP]; Zanoni, Maria V. B. [UNESP] (Royal Society of Chemistry (RSC), 2020)
Herein, we present an approach for the analytical determination and quantification of semi-permanent hair dyes in wash water samples released during washing of dyed hair employing a liquid chromatography-tandem mass spectrometry-selected reaction monitoring (LC-MS/MS-SRM) method with electrospray ionization detection. Specifically, Basic Blue 99 (BB 99), Basic Brown 16 (BB 16), Basic Red 76 (BR 76), Basic Yellow 57 (BY 57) and Acid Violet 43 (AV 43) are hair dyes with properties known to be harmful to human health and the environment. The hair dyes are present in commercial formulation and are discharged into the effluents without fully effective treatment. The detection and quantification by the LC-MS/MS technique show a linear relationship for each studied hair dye in the concentration range from 1 to 200 ng mL-1 in aqueous solution. The limits of detection and quantification were found from 0.66 to 20 ng mL-1 and from 2.0 to 63 ng mL-1, respectively, values that are compatible with the level required in wash water analysis. The method was applied in samples collected from 5 successive washings of hair dyed with a commercial formulation using the established procedure. BB 99 and BY 57 dyes have lower fixation on the scalp and hair, showing 866 ng mL-1 and 145 ng mL-1 release on the first day of washing, respectively. The accumulation of dye and slow release after washing can lead to future problems for both the environment and living organisms. This journal is